Expression, modulation, and clinical correlates of the autophagy protein Beclin‐1 in esophageal adenocarcinoma. Issue 11 (19th November 2015) - Weh, Katherine M.; Howell, Amy B.; Kresty, Laura A.
Abstract : Esophageal adenocarcinoma (EAC) is characterized by rapidly increasing incidence and mortality rates and poor survival. Efficacious preventive and treatment options are urgently needed. An increasing number of pharmacologic agents targeting cancer cell death via autophagy mechanisms are being evaluated in hopes of circumventing apoptotic and therapeutic resistance. We report for the first time, loss of Beclin‐1, a key mediator of autophagy, was significantly linked to prognostic factors in EAC. Specifically, Beclin‐1 expression loss occurred in 49.0% of EAC patients versus 4.8% of controls. There was a significant inverse correlation between loss of Beclin‐1 with histologic grade and tumor stage supporting a tumor suppressive role for Beclin‐1. Autophagy modulation linked to cell death was examined in EAC cell lines following treatment with a proanthocyanidin‐rich cranberry extract, C‐PAC, and the commonly used autophagy inducer, rapamycin. C‐PAC induced Beclin‐1‐independent autophagy in EAC cells characterized by reduced phosphorylation at serine 15 and 93, and significant cell death induction. In contrast, rapamycin‐induced autophagy resulted in concomitant, increases in total Beclin‐1 levels as well as Beclin‐1‐phosphorylation in a cell line specific manner, leading to long‐term cell survival. Furthermore, autophagic LC3‐II was induced by C‐PAC following siRNA suppression of Beclin‐1 in EAC cells. Together these data support a prognostic role of Beclin‐1 in EAC with evidence that Beclin‐dependent autophagy induction is agent specific. Future studies are necessary to fully interrogate the role autophagy plays in the progression of normal tissue to EAC and how specific agents targeting autophagic mechanisms can be efficaciously applied for cancer prevention or treatment. © 2015 Wiley Periodicals, Inc.